PRINCIPLES OF TEACHING WRITTEN LANGUAGE IN A FOREIGN LANGUAGE AS A SOCIAL PRACTICE WITHIN THE FRAMEWORK OF BILINGUAL EDUCATION AT UNIVERSITIES - Sultanova Nargiza Toxirjonovna; Saydivaliyeva Barno Saidbaxramovna (Galaxy International Interdisciplinary Research Journal, 2024)
Teaching written language in a foreign language within the realm of bilingual university education is a nuanced and intricate procedure demanding a robust research approach for optimal learning results. This article seeks to delve into the guiding principles of instructing written language as a social practice within the context of bilingual education at universities. The exploration will involve a thorough examination of the current body of literature on this subject, coupled with the proposal of a research methodology. This methodology aims to integrate key principles from communicative language teaching, task-based learning, and sociocultural theory to comprehensively understand the dynamics of teaching written language in a foreign language within the framework of bilingual education at universities.